HOW DECISION MAKING TO THE AUDIT FEE, AUDIT COMMITTEE ON A AUDIT QUALITY - Aprilya Dwi Yandari; Erina Sudaryati (Universitas Jember, 2017)
This article writes related the purpose of writing is to measure the extent of audit fees, audit committee on audit quality in a decision making. When to pay a fee should not be done by an auditee, because avoiding the existence of a form of problem to the loss of an auditor independence. Especially for clients who have opinions other than unqualified (WTP). It may also encourage an auditee to pressure the auditor, such as the form of pressure that will replace his or her public accounting firm with another accounting firm. Fee audit and audit committee are very influential in audit quality, when the actual audit cost is higher than normal audit cost. And then, audit fee of expensive can create an incentive to the auditor to agree on client pressure in a form of report result so that it can result to quality audit. In addition, audit fees also arise over a clients business risk relationship which has important implications for the obligation of an independent auditor for an audit that has been allegedly negligent in doing so, as well as on audit fees which theoretically relate to both an audit effort and a business's risk auditors. Keywords: Fee Audit, Audit Committee, Audit Quality, Financial Statements